VLADIMÍR SKALIČKA AND LANGUAGE CONTACT - Boček, Vít (Bohemica Olomucensia, 2022)
The paper maps the view of Vladimír Skalička, one of the main figures of the second generation of the Prague School, on the four related questions of language convergence and contact (linguistic areas, mixing of languages and dialects, causes of linguistic change, and borrowing). Skalička's ideas on language contact are presented in the context of his work, especially his typological theory and his approach to the question of language development. Also discussed and evaluated is the place that Skalička's thinking on language contact has in a wider context, namely in the Prague School. It is shown that these are not antiquated opinions but a living heritage that can be further developed.
Keywords: Vladimír Skalička; typology; language contact; borrowing; linguistic area; Prague School